Cotidiano de trabalho de profissionais da atenção primária à saúde em territórios rurais, no nordeste brasileiro - Silva, João Paulo Lopes da (2023)
The rural setting has historically been marked by popular clashes, social disparities and health inequalities. The rural population has long lacked the attention of public policies, especially the Unified Health System, due to unfavourable health conditions and the organization of Primary Health Care services. In rural areas, despite the expansion of the Family Health Strategy units, the dispersion of the population and the vast territorial area and poorly qualified management have been aggravating factors for the coverage of the Strategy, which is insufficient for resolutive Primary Care. The aim of this study was to understand the day-to-day work of Family Health Strategy professionals in rural areas of municipalities in the north-east of Brazil. It was a qualitative study set in four municipalities located in the interior of the state of Paraíba: Juru, Manaíra, Princesa Isabel and Tavares. One Family Health Strategy team from the rural areas of each municipality took part in the research, totaling twenty-three interviewees. The semi-structured interviews were conducted between May and July 2022, and the empirical material was organized using Atlas.ti22® software and based on Content Analysis. The results are presented in three thematic axes: Constructions and Organization of Work in the Family Health Team in a Rural Territory; Professional View on the Specificities of Caring for the Rural Population; Challenges and potential of working in the Family Health Strategy in a rural territory. For each axis, categories emerged which, consequently, gave rise to subcategories that emerged from the speeches. The meanings produced by the narratives showed that the rural territory studied is permeated by socio-spatial barriers and singularities that influence the organization of the work process and the schedule in the Family Health Strategy. There is fragmentation in the work planning process of some teams, especially in oral health. Decentralized actions, such as home visits and care at anchor points, were highlighted as a way of overcoming sociogeographical barriers. The study also revealed that difficulties such as sociogeographic access related to transportation and commuting, infrastructure problems at the anchor units, lack of resources and professional turnover are common difficulties found in Brazilian territories that compromise the longitudinality of care. As for the potentials, the most noteworthy were the professional bond, the importance of teamwork and the provision and retention of medical professionals through the Doctors for Brazil program. Despite the challenges posed by working in rural areas and given the specific characteristics of this territory and the working conditions, the professionals find satisfaction in their work.